Effects of chlorphentermine on the rat lung - Heath, Donald (1973)
Heath, D., Smith, P., and Hasleton, P. S. (1973).Thorax, 28, 551-558. Effects of chlorphentermine on the rat lung. Chlorphentermine hydrochloride (`Lucofen') is a sympathomimetic agent which is used in the treatment of obesity at a dosage of 25 mg thrice daily. When this drug, which is available on the British market, was administered intraperitoneally to rats in a dosage of 50 mg per kg body weight for 50 days, they all developed striking pathological changes in the lungs. Numerous large cells with foamy cytoplasm appeared in the alveolar spaces. Groups of them clumped together and disintegrated to pack the alveoli with granular eosinophilic material. The identification of these cells proved to be difficult even by electron microscopy, and this ultrastructural study is described separately in the following paper. During our acute experiments the rats did not develop right ventricular hypertrophy or hypertensive pulmonary vascular disease.